2006
DOI: 10.1194/jlr.m500512-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of LXR agonists on cellular cholesterol handling: a stable isotope tracer study

Abstract: The liver X receptors (LXRs) a and b are responsible for the transcriptional regulation of a number of genes involved in cholesterol efflux from cells and therefore may be molecular targets for the treatment of cardiovascular disease. However, the effects of LXR ligands on cholesterol turnover in cells has not been examined comprehensively. In this study, cellular cholesterol handling (e.g., synthesis, catabolism, influx, and efflux) was examined using a stable isotope labeling study and a two-compartment mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 47 publications
6
15
1
Order By: Relevance
“…In the present study we observed that T0901317-treatment induced ABCA1 in myotubes, SGBS, HepG2 and CaCo-2 cells, as well as ABCG1 in SGBS and CaCo-2 cells, in accordance with previous reports [7,[40][41][42]. Due to the beneficial effects of LXR activation on cholesterol homeostasis, LXR antagonists could be suspected to exert a negative effect on whole body cholesterol homeostasis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study we observed that T0901317-treatment induced ABCA1 in myotubes, SGBS, HepG2 and CaCo-2 cells, as well as ABCG1 in SGBS and CaCo-2 cells, in accordance with previous reports [7,[40][41][42]. Due to the beneficial effects of LXR activation on cholesterol homeostasis, LXR antagonists could be suspected to exert a negative effect on whole body cholesterol homeostasis.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment with T0901317 increased apoA1-dependent cholesterol efflux from human myotubes, as well as SGBS and CaCo-2 cells. We did not observe LXR-mediated elevation of apoA1-dependent cholesterol efflux from HepG2 cells, contrary to a previous report [40]. LXR activation has previously been shown to enhance apoA1-dependent cholesterol efflux from murine myotubes [22], HepG2 cells [40], murine 3T3-L1 adipocytes [42] and basolateral cholesterol efflux from CaCo-2 cells [41], but has not, to our knowledge, been studied in human adipocytes or myotubes.…”
Section: Discussioncontrasting
confidence: 86%
“…The absence of low plasma HDL-C in LAL-deficient mice is consistent with these observations, because mouse hepatic ABCA1 is reported to be unresponsive to LXR stimulation (45,46) and would not be expected to show reduced expression in the face of reduced flux of cholesterol out of lysosomes and oxysterol generation with LAL deficiency. Human hepatocyte ABCA1, conversely, is responsive to LXR activation in both primary human hepatocytes (47,48) and HepG2 cells (49,50). Human hepatocyte ABCA1 would therefore be expected to show reduced expression in the face of reduced LAL (and NPC1) activity and the reduced production of oxysterol agonist of LXR, which we have demonstrated here in fibroblasts.…”
Section: Discussionmentioning
confidence: 68%
“…Aravindhan et al [44] recently showed in HepG2 cells that cellular cholesterol fluxes were altered by LXR activation and that the increase in cholesterol synthesis did not compensate for the increased cellular cholesterol efflux, resulting in a net cellular cholesterol loss. We have previously demonstrated that LXR activation increased levels of cholesterol esters from labelled palmitic acid in human myotubes [33].…”
Section: Discussionmentioning
confidence: 99%